Computational Investigation on Fully Developed Periodic Laminar Flow Structure in Baffled Circular Tube with Various BR - Withada Jedsadaratanachai; Nuthvipa Jayranaiwachira; Pongjet Promvonge (My University, 2014)
This paper presents a 3D numerical analysis of fully developed periodic laminar flow in a circular tube fitted with 45° inclined baffles with inline arrangement. The computations are based on a finite volume method, and the SIMPLE algorithm has been implemented. The characteristics of fluid flow are presented for Reynolds number, Re = 100–1000, based on the hydraulic diameter ( D ) of the tube. The angled baffles were repeatedly inserted at the middle of the test tube with inline arrangement to generate vortex flows over the tested tube. Effects of different Reynolds numbers and blockage ratios ( b / D , BR) with a single pitch ratio of 1 on flow structure in the tested tube were emphasized. The flows in baffled tube show periodic flow at x / D ≈2-3, and become a fully developed periodic flow profiles at x / D ≈6-7, depending on Re, BR and transverse plane positions. The computational results reveal that the higher of BR and closer position of turbulators, the faster of fully developed periodic flow profiles.
Keywords: Baffle; Turbulator; Position (finance); Fluid Dynamics and Vibration Analysis